UNIFORM ACCOUNTING IN A TRADE ASSOCIATION. - Whiting, Grafton (The Accounting Review, 1926)
Abstract The paperboard group manufactures a heavy kraft and chipboard called liners, which form the outer and inner surface of combined board in the container industry; also a chipboard used in containers and a manila and cupboard with a special surface finish for folding boxes. The container group uses the liners and chip by passing even layers together to make and heavier board called solid fiberboard, or by Inserting a corrugated or fluted straw sheet between two liners there is made a corrugated board. The folding box group accepts the board as made by the mills, and without combining It, print and cut into finished product. The term container is used to designate a box or outer package made of paper fiber, and while limited In gross dimensions may be of any size or shape. The container group has the largest membership of our three divisions and represents about seventy five percent of the output of the country. This totaled in 1924 1,260,000 tons. It is with this group that the accounting work has been done and principally in connection with the corrugated branch.